Understanding the outcome of police safeguarding notifications to social services in South Wales. (June 2020) - Ford, Kat; Newbury, Annemarie; Meredith, Zoe; Evans, Jessica; Hughes, Karen; Roderick, Janine; Davies, Alisha R; Bellis, Mark A
In the UK, demand for the police has changed, with the majority of calls now vulnerability-related. Police safeguarding notifications (N=3, 466) over a one-year period for a local authority in Wales were matched to social care records. Over half (57.5%) of notifications were referred to social services and only 4.8% received social service input (e.g. social worker intervention). Over a third of individuals had repeat notifications in the study year. Findings evidence high levels of police-identified vulnerability and an imbalance in vulnerability-related risk thresholds across agencies. Furthermore, some individuals require more appropriate action to mitigate the risk of future safeguarding notifications.